IDENTIFYING FACTORS OF RISK MANAGEMENT IN SECONDARY CITIES TO FACE THE ENERGY CRISIS IN REALIZING A RESILIENT CITY - Rahmawan, Aditya Zulmi (Airlangga Development Journal, 2024)
The challenge of the energy crisis will be a phase experienced by cities. This can be seen in the projected urban population which continues to increase by 67%. This will be a shock as well as a new pressure for city life in addition to the burden of climate change. This study aims to provide a new approach and steps in assessing the energy crisis through risk management. The system of risk management will help make it easier to analyze the energy security situation and concepts that must be faced during an energy crisis. The establishment of this management system to prevent and control the energy crisis indicated that there were still misunderstandings and disagreements regarding the factors that should be a risk. This risk management consists of the concept of strategy, goal setting, resource requirements, risk identification, risk assessment, action planning, and risk communication that dominate various literatures. The results of the identification of risk management factors will make it easier to understand the strategies and policies that will be applied to improve and improve the quality status of urban management in order to create a resilient city. Keywords: risk management, secondary city, energy crisis, resilient city